QUALITY OF SANTRI IN MODERN ISLAMIC BOARDING SCHOOLS: QUALITY OF ACADEMIC SERVICES AND LEARNING MANAGEMENT - Badrudin; Asep Encu; Neng Gustini; Dini Munawaroh (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the effect of the quality of academic services and learning management on the quality of modern pesantren graduates. The quality of academic services is seen by five leading indicators: tangibles, reliability, responsiveness, assurance, and empathy. Meanwhile, the quality of graduates is seen by three indicators: attitude, knowledge, and skills. The study was conducted at the Modern Al-Ikhlash Putri Islamic Boarding School, Kuningan Regency. The number of respondents is 61 with the calculation of the slovin formula. Data collection techniques in this study used a questionnaire. Data analysis was carried out by testing the validity, reliability, and multiple linear regression tests assisted by the SPSS application. The research results show that the quality of academic services and learning management simultaneously influence the quality of modern pesantren graduates. It means that pesantren must improve their academic quality to have qualified graduates. Learning management should be used to develop new learning theories.